The role of age on neuromuscular performance decay induced by a maximal intensity sprint session in a group of competitive endurance athletes - Leonardo Cesanelli; Nerijus Eimantas; Angelo Iovane; Giuseppe Messina; Danguole Satkunskiene (European Journal of Translational Myology, 2022)
Age-related changes in the neuromuscular system functions may affect profoundly high-level athletes' performance across their careers. The present study aimed to analyse the fatiguing effect of a maximal intensity sprint session (MISS) on competitive athletes of different ages. Thirty-one competitive endurance athletes completed a knee extensors and flexors' maximal-voluntary-isometric-contraction (MVC) test before and after a maximal-intensity-sprint-session (MISS) consisting of 4x15s Wingate-tests. The data have been stratified considering three age categories (18-28, n=11, 29-38; n=10; 39-43, n=10). Overall, both quadricep and hamstring muscles early and late rate of torque development (RTD) dropped significantly more than the maximal voluntary torque (MVT) (p<.05). Age had a significant effect on early RTD, with older athletes exhibiting greater RTD (p<.05). A significant effect of age also emerged for the changes in surface sEMG variables, in which the frequency spectrum variables dropped significantly more than the sEMG amplitude (RMS) (p<.05). The dynamics of changes in neuromuscular performance markers after a MISS suggested that getting older competitive athletes may potentially experience a greater loss in early explosive strength compared to maximal or late explosive strength.